Nauczyciele wychowania przedszkolnego i klas I–III wobec edukacji matematycznej z wykorzystaniem nowych technologii - Monika Czajkowska; Klaudia Mróz (Problemy Wczesnej Edukacji)
In this article, we present partial results of research aimed at identifying how pre-school education and primary school (grades I–III) teachers use new technologies resources in mathematics education. 110 teachers participated in the study. The basic research method was an internet questionnaire. Our research has shown that many pre-school education and primary school (grades I–III) teachers, especially those with 10 years of work experience and more, show a high pedagogical awareness. When conducting mathematics education classes, they use both conventional teaching aids and new technologies resources, and try to maintain the right proportions. However, in the times of the COVID-19 pandemic, conducting remote math education for a significant proportion of the teachers surveyed turned out to be a big challenge. The typical difficulties to teaching mathematics were combined with difficulties related to distance education and difficulties resulting from the attitude (reluctance) of parents, and sometimes children, to mathematics or learning this subject.